Say hello to my little friend : a novel - Crucet, Jennine Capó (Simon & Schuster, 2024)
Scarface meets Moby Dick in this groundbreaking, darkly comic novel about a young man's attempt to capitalize on his mother's murky legacy--a story steeped in Miami's marvelous and sinister magic. Failed Pitbull impersonator Ismael Reyes--you can call him Izzy--might not be the Scarface type, but why should that keep him from trying? Growing up in Miami has shaped him into someone who dreams of being the King of the 305, with the money, power, and respect he assumes comes with it. After finding himself at the mercy of a cease-and-desist letter from Pitbull's legal team and living in his aunt's garage-turned-efficiency, Izzy embarks on an absurd quest to turn himself into a modern-day Tony Montana. When Izzy's efforts lead him to the tank that houses Lolita, a captive orca at the Miami Seaquarium, she proves just how powerful she and the water surrounding her really are--permeating everything from Miami's sinking streets to Izzy's memories to the very heart of the novel itself. What begins as Izzy's story turns into a super-saturated fever dream as sprawling and surreal as the Magic City, one as sharp as an iguana's claws, and as menacing as a killer whale's teeth. As the truth surrounding Izzy's boyhood escape from Cuba surfaces, the novel reckons with the forces of nature, with the limits and absence of love, and with the dangers of pursuing a tragic inheritance. Wildly narrated and expertly rendered, Say Hello to My Little Friend is Jennine Capó Crucet's most daring, heart-breaking, and fearless book yet.